KEPEMILIKAN RUMAH TUNGGAL ORANG ASING DI INDONESIA DALAMPERSPEKTIF HUKUM PERTANAHAN - I Gede Yuda Sedana Putra; I Nyoman Suandika; I Kadek Dedy Suryana; Komang Edy Dharma Saputra (Jurnal Ilmiah Raad Kertha, 2023)
In Indonesia, regulations regarding land are regulated in the Basic Agrarian Law, namely Law Number 5 of 1960. In principle, the Basic Agrarian Law, namely Law Number 5 of 1960, regulates the prohibition of land ownership by foreign nationals. This is a reflection of the principle of nationalism as stipulated in Article 21 Paragraph (1), which states that only Indonesian citizens can have property rights. The spirit of nationalism emphasized in Article 21 Paragraph (1) has given Indonesian citizens full rights to manage the earth and outer space without discriminating between men and women as well as fellow Indonesian citizens, both original and descendants resulting from a marriage that legitimate. Furthermore, when examined in more depth regarding the matter above, the essence of Article 21 Paragraph (1) in the Basic Agrarian Law aims to maintain that land remains the property of the state or Indonesian Citizens, because if the land is controlled by foreigners legally full or with a tendency to be long, it is feared that people's welfare will decrease in the management of land